Evidence for multipotent endodermal stem/progenitor cell populations in human gallbladder - Carpino, Guido; Cardinale, Vincenzo; Gentile, Raffaele; Onori, Paolo; Semeraro, Rossella; Franchitto, Antonio; Wang, Yunfang; Bosco, Daniela; Iossa, Angelo; Napoletano, Chiara; Cantafora, Alfredo; D’Argenio, Giuseppe; et al. (Journal of hepatology, 2014)
Multipotent stem/progenitor cells are found in peribiliary glands throughout human biliary trees and are able to generate mature cells of hepato-biliary and pancreatic endocrine lineages. The presence of endodermal stem/progenitors in human gallbladder was explored. Gallbladders were obtained from organ donors and laparoscopic surgery for symptomatic cholelithiasis. Tissues or isolated cells were characterized by immunohistochemistry and flow cytometry. EpCAM+ (Epithelial Cell Adhesion Molecule) cells were immunoselected by magnetic microbeads, plated onto plastic in self-replication conditions and subsequently transferred to distinct serum-free, hormonally defined media tailored for differentiation to specific adult fates. In vivo studies were conducted in an experimental model of liver cirrhosis. The gallbladder does not have peribiliary glands, but it has stem/progenitors organized instead in mucosal crypts. Most of these can be isolated by immune-selection for EpCAM. Approximately 10% of EpCAM+ cells in situ and of immunoselected EpCAM+ cells co-expressed multiple pluripotency genes and various stem cell markers; other EpCAM+ cells qualified as progenitors. Single EpCAM+ cells demonstrated clonogenic expansion ex vivo with maintenance of stemness in self-replication conditions. Freshly isolated or cultured EpCAM+ cells could be differentiated to multiple, distinct adult fates: cords of albumin-secreting hepatocytes, branching ducts of secretin receptor+ cholangiocytes, or glucose-responsive, insulin/glucagon-secreting neoislets. EpCAM+ cells transplanted in vivo in immune-compromised hosts gave rise to human albumin-producing hepatocytes and to human Cytokeratin7+ cholangiocytes occurring in higher numbers when transplanted in cirrhotic mice. Human gallbladders contain easily isolatable cells with phenotypic and biological properties of multipotent, endodermal stem cells.